Urinary concentrations of pyrethroid metabolites and its association with lung function in a Canadian general population. Issue 2 (14th January 2016) - Ye, Ming; Beach, Jeremy; Martin, Jonathan W; Senthilselvan, Ambikaipakan
Abstract : Objectives: While there is increasing concern about the health impact of pyrethroid insecticides, little is known about their effect on lung function. In this cross-sectional study, urinary concentrations of pyrethroid (PYR) metabolites and their associations with lung function were examined among a Canadian general population using data from the Canadian Health Measures Survey (CHMS). Methods: Urinary concentrations of 5 pyrethroid metabolites (3-PBA, 4-F-3-PBA, cis -DCCA, trans -DCCA and cis -DBCA) were available for 5436 CHMS participants aged 6–79 years. Lung function parameters considered were forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1 ), FEV1 /FVC ratio and forced expiratory flow between 25% and 75% of FVC. Multiple linear regression analyses were used to examine associations between PYR concentrations and lung function in children (6–11 years), adolescents (12–19 years) and adults (20–79 years), respectively. Results: Almost all CHMS participants (99.8%) had PYR metabolites detectable in urine. In multiple linear regression analyses, 1 unit increase in log transformed urinary concentration (nmol/g creatinine) of total pyrethorid metabolites (ΣPYR) was associated with a 17.4 mL reduction in FEV1 (p=0.045) in children, a 37.1 mL reduction in FVC (p=0.05) in adolescents and a 0.3% (p=0.01) increase in FEV1 /FVC ratio in adults. Conclusions: These results show evidence of widespread exposures to pyrethroid insecticides among the Canadian general population. Pyrethroid exposures were associated with lower FEV1 in children, lower FVC in adolescents and relatively higher FEV1 /FVC ratio in adults. Further research is necessary to confirm the potential effect of pyrethroid insecticides on lung function reported in this study.